2017
DOI: 10.1038/cmi.2017.36
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ T cells memorize obesity and promote weight regain

Abstract: Body weight regain often causes failure of obesity therapies while the underlying mechanism remains largely unknown. In this study, we report that immune cells, especially CD4+ T cells, mediate the 'memory' of previous obese status. In a weight gain-loss-regain model, we found that C57BL/6J mice with an obesity history showed a much faster rate of body weight regain. This obesity memory could last for at least 2 months after previously obese mice were kept at the same body weight as non-obese mice. Surprisingl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 57 publications
5
45
0
Order By: Relevance
“…Moreover, as is common in observational human studies, it is difficult to prove causality. However, considering the present findings and those from prior weight gain-loss obese mice studies (57), in which CD4 + T cells were shown to mediate obesity memory and promote weight regain, our results are highly suggestive of a similar relationship in humans. As the gut microbiota seems to be involved in the induction of obesity and interacts with the gut immune system (59), regulating the formation of effector memory T-cell subsets, studies investigating the modulation of the gut microbiome through diet, pre-and probiotics, antibiotics, surgery, and fecal transplantation are warranted.…”
Section: Discussionsupporting
confidence: 78%
“…Moreover, as is common in observational human studies, it is difficult to prove causality. However, considering the present findings and those from prior weight gain-loss obese mice studies (57), in which CD4 + T cells were shown to mediate obesity memory and promote weight regain, our results are highly suggestive of a similar relationship in humans. As the gut microbiota seems to be involved in the induction of obesity and interacts with the gut immune system (59), regulating the formation of effector memory T-cell subsets, studies investigating the modulation of the gut microbiome through diet, pre-and probiotics, antibiotics, surgery, and fecal transplantation are warranted.…”
Section: Discussionsupporting
confidence: 78%
“…Moreover, phenotypic switching of ATMs into the alternatively activated M2 is sufficient to modulate adipose tissue function. 22,42,43 In the eWAT of diabetic mice, miR-99a mimics significantly attenuated F4/80 + CD11b + CD11c + CD206 − M1 and enhanced the F4/80 + CD11b + CD11c − CD206 + M2 macrophage populations, while significantly decreasing iNOS, MCP-1, and TNFα and significantly increasing ARG-1, YM-1, and PPARγ mRNA expression. In miR-99a-treated db/db mice, an attenuated CD86 and enhanced CD301 staining in eWAT again suggested the suppression of M1 macrophage and activation of the M2 phenotype.…”
Section: Discussionmentioning
confidence: 98%
“…Reduction of inflammatory gene expression by SP may be due to changes in the population of immune cells found in the spleen, which has been demonstrated to change in response to obesity (36,37) . Alternatively, components found in SP may also reduce inflammatory gene expression in splenocytes by inhibiting the Toll-like receptor 4 signalling pathways.…”
Section: Discussionmentioning
confidence: 99%